2010
DOI: 10.1016/j.transproceed.2010.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Reticulated Platelets and Platelet Reactivity in Renal Transplant Recipients Receiving Antiplatelet Therapy

Abstract: We documented the presence of higher concentrations of RPs in transplant recipients compared with a control population, and a significant association between RPs and platelet function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…IPF was assessed in patients who underwent renal transplantation; the Sysmex 2100 XE was also the device used in this study [24]. A higher IPF was detected in transplant recipient group when compared to a healthy control group, IPF values for both groups were not reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IPF was assessed in patients who underwent renal transplantation; the Sysmex 2100 XE was also the device used in this study [24]. A higher IPF was detected in transplant recipient group when compared to a healthy control group, IPF values for both groups were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…high platelet turnover) has been explained by increased generation of new platelets that are unaffected by antiplatelet therapy, possibly because of the uninhibited activity of COX1, and COX2 in the newly formed platelets [13,14,[20][21][22][23][24][25][26]. Recent studies showing that platelet mRNA is actively spliced and translated in response to platelet stimulation [27,28] also raises the possibility that prothrombotic pathways may also be activated in this platelet population despite partial blockade of P2Y12 by the active metabolite of clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…Increased circulating RPs has been proposed as an important mechanism associated with cardiovascular risk in these patients [20]. A significant association between RP count and platelet function supports the role for platelets in cardiovascular complications in kidney transplantation [58].…”
Section: Kidney Dysfunctionmentioning
confidence: 94%
“…It has been suggested that RPs are present in inflammation and interact with leukocytes and endothelial cells [19]. Moreover, RPs have reduced response to antiplatelet drugs, ie, aspirin, possibly due to their greater reactivity and impaired cyclooxygenase-1 and -2 inhibition [20].…”
Section: Properties Of Reticulated Plateletsmentioning
confidence: 99%
“…Степень подавления агрегации тромбоцитовпри изолированномпримененииаспирина (ингибитора циклооксигеназы и синтезатромбоксана А2) в зависимости от содержания РТ исследовали в группе здоровых доноров [10] и у больныхсо стабильнойстенокардией [10,27], диабетом [20] и перенесших трансплантацию почки [28]. Во всех работах повышение содержания РТ было ассоциировано с уменьшением антиагрегантногодействияаспирина.…”
Section: ретикулярные тромбоциты и эффективность антитромбоцитарных препаратовunclassified